Here and There in Mexico : the Travel Writings of Mary Ashley Townsend. - Townsend, Mary Lee (University of Alabama Press, 2007)
Mary Ashley Townsend was a novelist, newspaper columnist, and poet laureate of New Orleans who made several trips to Mexico with her daughter Cora during the last two decades of the 19th century. She collected her impressions of many aspects of life in that country-flora, fauna, architecture, people at work and play, fashion, society, food-and wrote about them during a time when few women engaged in solo travel, much less the pursuit of travel writing. Her collected work was still in progress when she died in a train accident in 1901, and was never published. Renowned Latin A.